2022
DOI: 10.3988/jcn.2022.18.6.610
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Wall Changes on Serial High-Resolution MRI and the Use of Cilostazol in Patients With Adult-Onset Moyamoya Disease

Abstract: Background and Purpose The natural course of adult-onset moyamoya disease (MMD) is unknown, and there is no medical treatment that halts its progression. We hypothesized that progressive shrinkage of large intracranial arteries occurs in adult-onset MMD, and that cilostazol inhibits this process. Methods Serial high-resolution magnetic resonance imaging (HR-MRI) was performed on 66 patients with MMD: 30 patients received cilostazol, 21 received other antiplatelets, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…On HR-VWI, MMD is characterized by strong enhancement in the distal ICA and extension into the proximal M1 or A1 [ 56 ]. In general, it exhibits concentric enhancement.…”
Section: Utilization Of High-resolution Vessel Wall Mr Imaging In Cli...mentioning
confidence: 99%
See 2 more Smart Citations
“…On HR-VWI, MMD is characterized by strong enhancement in the distal ICA and extension into the proximal M1 or A1 [ 56 ]. In general, it exhibits concentric enhancement.…”
Section: Utilization Of High-resolution Vessel Wall Mr Imaging In Cli...mentioning
confidence: 99%
“…This finding provides insights into deciding whether to discontinue antiplatelet therapy, especially in young patients, who are more susceptible to intracranial dissections. In MMD, a study showed that the progression of negative remodeling on follow-up HR-VWI was slower when cilostazol was administered than when other antiplatelet agents were used [ 56 ]. Another study showed that rapid progression of arterial stenosis increased the risk of recurrent stroke in patients with MMD [ 67 ].…”
Section: Utilization Of High-resolution Vessel Wall Mr Imaging In Cli...mentioning
confidence: 99%
See 1 more Smart Citation
“…For 3.0 T MR head imaging, there are several receiving coils, including 8, 16, and 32-channel head coils, or 16, 20, 24, and 64-channel high-resolution coils for imaging the head and neck. Presently, the 32-channel high-resolution coil is commonly used ( Kim et al, 2022 ; Liang et al, 2023 ). Studies have shown that, compared with 8-the channel head coil, the 32-channel head coil can increase SNR up to 3.4 times in the cortex and 1.4 times in the corpus callosum ( Wiggins et al, 2006 ); Compared with the 12-channel head coil, the 32-channel head coil increased the SNR in the middle of the brain by about 1.5 times ( Wiggins et al, 2006 ).…”
Section: Overview Of Hr-vwimentioning
confidence: 99%
“…Subsequent studies using HR-VWI were able to demonstrate the specific mechanism played by cilostazol in patients with MMD. It was demonstrated that cilostazol resulted in a significant increase in the outer diameter of the diseased vessel, a significant reduction in the degree of stenosis, and positive remodeling ( Kim et al, 2022 ). This is also the only study that used HR-VWI to analyze medical interventions for MMD.…”
Section: Application Of Hr-vwi In MMDmentioning
confidence: 99%